2009
DOI: 10.1007/s10751-009-9916-9
|View full text |Cite
|
Sign up to set email alerts
|

Ball milling induced interstitial atoms redistributions revealed by Mössbauer effect in Fe based alloys

Abstract: Interstitial alloys FeI x (I = C or N) have been obtained by ball milling process in the concentration range 0.125 ≤ x ≤ 0.5. With the here chosen processing protocol the asymptotic completion interstitial distribution is obtained after about 30 h and only depends on x and nature of interstitial (C or N) and not on reactants which only have to respect the aimed nominal composition of the mixture. Mössbauer spectrometry results have proven that the distribution observed for similar interstitial compositions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is also shown that low temperature aging, near and below 200uC, induced transformations taking place in connexion with mechanically driven phenomena likely to improve cold and temperate sintering and green density before higher temperature treatments. 13,14 It is worth underlining that any decomposition of iron nitride during the last stage of sintering, before final cooling must be imperatively avoided because the N 2 gas pressure released in open and specially closed porosities would severely damage mechanical strength and toughness. To improve the densification of the powder particles, a nickel deposit was added to the grain surface of the nitrided powder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also shown that low temperature aging, near and below 200uC, induced transformations taking place in connexion with mechanically driven phenomena likely to improve cold and temperate sintering and green density before higher temperature treatments. 13,14 It is worth underlining that any decomposition of iron nitride during the last stage of sintering, before final cooling must be imperatively avoided because the N 2 gas pressure released in open and specially closed porosities would severely damage mechanical strength and toughness. To improve the densification of the powder particles, a nickel deposit was added to the grain surface of the nitrided powder.…”
Section: Discussionmentioning
confidence: 99%
“…TMS allows the quantification of iron based phases and the determination of theirs interstitial atoms amounts. [13][14][15] Furthermore TMS it is providing a unique way to characterise interstitial atoms redistributions ordering or clustering induced by ageing and ball milling.…”
Section: Methodsmentioning
confidence: 99%